Glassy and Glass Composite Nuclear Wasteforms - Ojovan,MI; Lee,WE (2011)
The current status of vitrification techniques for immobilisation of nuclear wastes in glasses and glass composite materials (GCM) are reviewed. One-stage and two-stage processes are described along with the compositions and properties of the resulting glassy wasteforms. Techniques for assessing wasteform durability are discussed along with the mechanisms of corrosion on contact with groundwater.